E-Travel Riau Berbasis Mobile Menggunakan Metode Dijkstra - Marni, Prina; Asnal, Hadi; Erlinda, Susi; Agustin, Agustin (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
Travel is one of the transportation that is often used by study tours or tourism in Riau Province. Travel is not only engaged in ordering but also in the field of delivery of goods. But what often happens to travel is that bookings are still done manually. The ordering process is carried out by telephone, then the admin records the address of the passenger to be picked up and the admin immediately confirms to the driver to pick up the passenger. The purpose of this study is to assist passengers in ordering travel online and drivers can monitor and determine the location of prospective passengers. In this study, an android-based online travel booking application was created using the Dijkstra algorithm. The dijkstra algorithm is an algorithm used to solve the shortest path problem for a directed graph with non-negative edge weights. This algorithm is used by drivers to determine the fastest route in the process of picking up prospective passengers. The advantage of this Dijkstra method is that it can find the closest route from the starting point to the end point by comparing the smallest value between points that will be used as a route that will be passed by the travel driver in order to get to the destination faster. The results of this study are a travel application that makes it easier for users to book travel and makes it easier for drivers to determine the fastest route in picking up passengers